Tasawuf dalam Perspektif Sejarah Ibn Khaldun - Ulfa, Fadillah; Sa’ari, Che Zarrina Binti; b. Syed Abdul Rahman, Syed Mohammad Hilmi (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2021)
Sufism is a spiritual philosophy based on morals and intuition. It has affected the daily lives of Muslims and their behaviours as well. Actually, Sufism itself since its development has changed in terms of values, since it involves other knowledge which influences the purity of its teachings. To study the concept of Sufism and the history of its development, maintaining the purity of Sufism and returning it to the original teachings of tassawuf is needed especially in regards to Ibn Khaldunâ€™s views since he is one of the scholars who emphasises the discussion and study of Sufism seriously and comprehensively. It can be seen by his objective in evaluating Sufism and producing the point of view to Sufism. Even as a historian and social expert, he also discusses the questions of Sufism from the root of the problem and its impact on the social life of Muslims. This study aims to analyse Ibn Khaldunâ€™s views on the reality of Sufism and the history of its development with special reference to SyifÄ al-SÄil wa Taá¸¥dzÄ«b al-MasÄl. To achieve these objectives, the library research method incorporating data collection and data analysis was used. Data analysis was done inductively and deductively. The results of the study have shown that Ibn Khaldun puts his own definition of Sufism comprehensively which is known as Mujahadah. The concept of mujahadah, according to him runs parallel to the history of the knowledge development and practices of Sufism. It began with mujahadah of taqwa, known among the early Sufis as zuhud and waraâ€˜. Furthermore, mujahadah istiqamah and kashf are known as ladunÄ« or Sufism.